1979
DOI: 10.1113/jphysiol.1979.sp012756
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus toxin and synaptic inhibition in the substantia nigra and striatum of the rat.

Abstract: SUMMARY1. The effects of tetanus toxin were determined on GABA-mediated synaptic inhibition of substantia nigra neurones evoked by striatal stimulation and on the presumed dopamine-and 5-hydroxytryptamine-mediated synaptic inhibition of striatal neurones evoked by nigral and dorsal raphe nucleus stimulation, respectively, in the urethane-anaesthetized rat.2. Following an intranigral injection of tetanus toxin, striatal-evoked inhibition of substantia nigra neurones, which is sensitive to bicuculline, was rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…Tetanus toxin is considered to act by preventing the synaptic release of inhibitory amino acids (Osborne & Bradford, 1973;Curtis, 1971), and has been shown to abolish synaptic inhibition believed to be mediated by these amino acids at both spinal and supra-spinal sites (Curtis & de Groat, 1968;Curtis, Felix, Game & McCulloch, 1973; PREOPTIC AREA INHIBITORY MECHANISMS Davies & Tongroach, 1979). Reduction of the frequency of occurrence of synaptic inhibition in the preoptic-anterior hypothalamus by tetanus toxin provides valuable confirmatory evidence in support of the earlier suggestion that such inhibition is mediated by amino acid transmitters.…”
Section: Discussionsupporting
confidence: 57%
“…Tetanus toxin is considered to act by preventing the synaptic release of inhibitory amino acids (Osborne & Bradford, 1973;Curtis, 1971), and has been shown to abolish synaptic inhibition believed to be mediated by these amino acids at both spinal and supra-spinal sites (Curtis & de Groat, 1968;Curtis, Felix, Game & McCulloch, 1973; PREOPTIC AREA INHIBITORY MECHANISMS Davies & Tongroach, 1979). Reduction of the frequency of occurrence of synaptic inhibition in the preoptic-anterior hypothalamus by tetanus toxin provides valuable confirmatory evidence in support of the earlier suggestion that such inhibition is mediated by amino acid transmitters.…”
Section: Discussionsupporting
confidence: 57%
“…Since then it has been shown that many kinds of inhibitory synapses in the central nervous system (c.N.s.) are blocked by tetanus toxin (Brooks & Asanuma, 1962;Curtis & De Groat, 1968;Curtis, Felix, Game & McCulloch, 1973; Davies & Tongroach, 1979) while some excitatory synapses in the spinal cord and the substantia nigra are not affected (Brooks et al 1957;Geinisman,' D'yakonova & Kryzhanovsky, 1967;Curtis & De Groat, 1968; Kryzhanovsky, Kurchavyi & Sheikhon, 1973;Takano, 1976; Davies & Tongroach, 1979). Therefore, it has been generally considered that tetanus toxin does not act directly on excitatory synapses in the C.N.s.…”
Section: Introductionmentioning
confidence: 99%
“…However, excitation and perhaps degeneration could also arise without any net change in glutamate levels if the GABAmediated inhibitory input is reduced. We have tested this hypothesis using tetanus toxin which selectively blocks the GABAergic inhibitory tone in the CNS (Davies & Tongroach, 1979) and the release of GABA in rat hippocampal slices (Collingridge et al, 1981 (coordinates A = -4mm from the bregma, L = 2 mm from the midline, V = 2.4 mm below the dura mater according to the rat brain atlas of Paxinos & Watson, 1982; the volume of injection was 1l 4umin-1) by means of a Hamilton microsyringe (5 pl) mounted on a stereotaxic frame. Animals injected with bovine serum albumin (BSA), phosphate buffer (pH = 7.0; used to dissolve tetanus toxin) and neutralized tetanus toxin (the neutralization was carried out with a F(ab)' fragment of the native IgG antitetanus toxin as previously described by Gawade et al, 1985) were used as controls.…”
Section: Introductionmentioning
confidence: 99%